Modulating mechanical cues and oxygen availability to regulate chondrogenesis within MSC laden hydrogels - Irvine, Alan D. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2017)
Tissue engineering is a potential alternative to conventional surgical techniques for regenerating damaged tissues that lack the ability to spontaneously repair. MSCs are a promising cell source for tissue engineering strategies intended to treat a range of injuries and diseases. Within the synovial joint environment, a complex array of biochemical, environmental and biomechanical stimuli arise. If MSCs are to be successfully used in vivo, understanding the effects on their differentiation and function in response to these stimuli is vital. A central hypothesis of this thesis is that oxygen availability and mechanical stimulation can direct chondrogenic differentiation and hypertrophy of MSCs. This thesis examines the response of MSC-laden hydrogels to oxygen availability, substrate stiffness and dynamic compressive strain. The overall objective is to develop the precursor to an osteochondral graft by mechanically modulating chondrogenesis and hypertrophy of MSCs within a 3-dimensional hydrogel environment. To enable this, this thesis first systemically explored the response of MSCs undergoing chondrogenesis to altered levels of substrate stiffness, dynamic compression and oxygen availability. The application of dynamic compression after 21 days at different magnitudes in 20 % O2 to dynamic compression to MSC-laden agarose hydrogels was found to alter calcification in a magnitude dependent manner. High magnitudes (20 % strain) tended to reduce the increases in calcification produced at moderate strains. The thesis next explored the role of substrate stiffness in regulating chondrogenesis in altered oxygen environments. In MSC-laden, RGD-modified alginate hydrogels, it was found that soft hydrogels enhance early MSC chondrogenesis. Altering oxygen levels from from 20% to 5% altered the spatial distribution of cartilage-specific proteins producing a more homogenous tissue. In a subsequent study, dynamic compression applied after 5 days in 5% O2 only affected MSC chondrogenesis and hypertrophy in stiff, less chondrogenic MSC-laden hydrogels. Here, moderate strains (10%) enhanced MSC chondrogenesis and high strains (20%) reduced MSC hypertrophy in stiff MSC-laden hydrogels in comparison to moderate strains (10%). The next stage of the thesis explored tailoring substrate stiffness, oxygen availability and local dynamic compressive strain magnitude in a gradient fashion, with the hypothesis that a precursor to an osteochondral-like tissue could be produced. Varying substrate stiffness throughout the depth in these alginate hydrogels and applying dynamic compression lead to spatial changes in MSC differentiation, but failed to produce an effective osteochondral precursor. The final stage of this thesis involved impregnating a MSC-laden alginate hydrogel into a 3-D printed polymeric scaffolds with a gradient profile. This created an environment that modulated local strain magnitude alone. Spatial differences in MSC chondrogenesis in gradient mesh constructs alone were observed. GAG production was enhanced in regions of low strain and hypertrophy was reduced in areas of high strain. This thesis demonstrates that the MSC chondrogenesis and hypertrophy are mechano-regulated. It highlights the interdependence of oxygen availability, substrate stiffness and dynamic compression as well as the effect local variations in these stimuli can have on the development of engineered tissues. This work will aid in the understanding of MSC mechanobiology, optimum tissue engineering considerations for both cartilage and osteochondral tissue engineering and 3-D bioprinted scaffold design.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin